Functional Restoration following Global Cerebral Ischemia in Juvenile Mice following Inhibition of Transient Receptor Potential M2 (TRPM2) Ion Channels - Robert M. Dietz; James E. Orfila; Nicholas Chalmers; Crystal Minjarez; Jose Vigil; Guying Deng; Nidia Quillinan; Paco S. Herson (Neural Plasticity)
Hippocampal cell death and cognitive dysfunction are common following global cerebral ischemia across all ages, including children. Most research has focused on preventing neuronal death. Restoration of neuronal function after cell death is an alternative approach (neurorestoration). We previously identified transient receptor potential M2 (TRPM2) ion channels as a potential target for acute neuroprotection and delayed neurorestoration in an adult CA/CPR mouse model. Cardiac arrest/cardiopulmonary resuscitation (CA/CPR) in juvenile (p20-25) mice was used to investigate the role of ion TRPM2 channels in neuroprotection and ischemia-induced synaptic dysfunction in the developing brain. Our novel TRPM2 inhibitor, tatM2NX, did not confer protection against CA1 pyramidal cell death but attenuated synaptic plasticity (long-term plasticity (LTP)) deficits in both sexes. Further, in vivo administration of tatM2NX two weeks after CA/CPR reduced LTP impairments and restored memory function. These data provide evidence that pharmacological synaptic restoration of the surviving hippocampal network can occur independent of neuroprotection via inhibition of TRPM2 channels, providing a novel strategy to improve cognitive recovery in children following cerebral ischemia. Importantly, these data underscore the importance of age-appropriate models in disease research.